Validity and Reliability of the Isometric Prone Bench Pull Test - Lum, Danny; Aziz, Luqman (International Journal of Sports Medicine, 2020)
Isometric strength tests are gaining popularity in recent years. However, no study has validated any isometric strength tests to assess upper body pulling ability. The aim of this study was to investigate the validity and reliability of isometric prone bench pull. Twenty-three resistance trained athletes (age: 26±4 years, height: 1.75±0.07 m, body mass: 78.6±11.5 kg) were required to perform prone bench pull 1 repetition maximum and isometric prone bench pull tests during the familiarization and actual testing sessions. Isometric prone bench pull was performed at 90° and 120° elbow angles. Peak force and rate of force development measures were highly reliable with intra-correlation coefficient between 0.881–0.987. Peak force obtained from isometric prone bench pull at both elbow angles showed large correlations to prone bench pull 1 repetition maximum (r=0.833–0.858, p<0.01). Linear regression equations to predict 1RM performance from isometric prone bench pull peak force produced an estimated 1RM with a standard error of only 3–6% of the average prone bench pull 1 repetition maximum. The current findings show that isometric prone bench pull is a reliable test and can be used to predict prone bench pull performance.